The Application of Problem-Based Learning Model to Improve Learning Outcomes of Hindu Religious and Character (Budi Pekerti) Education of Fifth-Grade Students at SD Mahardika - Sudiarta, I Kadek; Pitriani, Ni Rai Vivien (Jayapangus Press, 2023)
The Hindu religious education learning process should be designed systematically to achieve the objectives (1) to develop and improve the quality of Sraddha (belief) and Bhakti (piety) of the people through providing, emphasizing, appreciating, and practicing the Hindu religious teachings, and (2) building a Hindu society that can realize the Moksartham Jagathita values in its life. Based on the pretest results in October on the student learning outcomes of Hindu religious and character (Budi Pekerti) education of fifth-grade students at SD Mahardika Denpasar, it showed that the level of student learning completeness was still below the Minimum Completeness Criteria (KKM). The cause of the low learning completeness values of students was that it was below the Minimum Completeness Criteria (KKM). It can be identified from most students who still have difficulty and often forget to understand the subject matter provided. The reason was that the teacher still functions as the primary source of learning that provides knowledge to students instead of being a student facilitator. Students only pay attention to explanations, accept the teacher’s examples, and are never directly involved in solving problems. This study aimed to determine how the best implementation of applying the Problem-Based Learning model improves the learning outcomes of Hindu religious and character (Budi Pekerti) education in fifth-grade students at SD Mahardika Denpasar. The research method used in this study was the Classroom Action Research (PTK) method. The research was conducted in several stages or cycles. Reflection on cycle I was carried out to determine the steps for improvement in cycle II. Based on the evaluation data of student learning outcomes that have been carried out from activities in cycle I and cycle II showed a significant increase. The evaluation results of the learning outcomes of fifth-grade students at SD Mahardika Denpasar in the 2022/2023 academic year showed an increase in the student learning outcomes in Hindu religious and character (Budi Pekerti) education lessons.